IDENTIFICATION OF STUDENTS’ EARLY BEHAVIOR AND CHARACTERISTICS - Ina Magdalena; Amalia Sri Wulandari; Dicha Noviantik; Netri Netri; Novitasari Novitasari (PROGRES PENDIDIKAN, 2022)
This study aims to determine the identification of the behavior and initial characteristics of students. Sindangsari III Elementary School, Tangerang Regency. The research method used is a qualitative method with descriptive data exposure. This data collection technique uses interviews, observation, and documentation. The sources of this data collection were obtained from sources / informants and from the research site. The results of this study were carried out quite well and neatly arranged. This study used the interview method to one of the teachers of SDN Sindangsari III. This interview is carried out directly / offline by approaching the source.